Anoctamin-6 Controls Bone Mineralization by Activating the Calcium Transporter NCX1 - Ousingsawat, Jiraporn (J Biol Chem, 2015)
Anoctamin-6 (Ano6, TMEM16F) belongs to a family of putative Ca(2+)-activated Cl(−) channels and operates as membrane phospholipid scramblase. Deletion of Ano6 leads to reduced skeleton size, skeletal deformities, and mineralization defects in mice. However, it remains entirely unclear how a lack of Ano6 leads to a delay in bone mineralization by osteoblasts. The Na(+)/Ca(2+) exchanger NCX1 was found to interact with Ano6 in a two-hybrid split-ubiquitin screen. Using human osteoblasts and osteoblasts from Ano6(−/−) and WT mice, we demonstrate that NCX1 requires Ano6 to efficiently translocate Ca(2+) out of osteoblasts into the calcifying bone matrix. Ca(2+)-activated anion currents are missing in primary osteoblasts isolated from Ano6 null mice. Our findings demonstrate the importance of NCX1 for bone mineralization and explain why deletion of an ion channel leads to the observed mineralization defect: Ano6 Cl(−) currents are probably required to operate as a Cl(−) bypass channel, thereby compensating net Na(+) charge movement by NCX1.